The father’s singing voice may impact premature infants’ brain more than their mother’s: A NICU single-arm exploratory study protocol and preliminary data on a singing and EEG framework based on the fundamental frequency of voice and kinship - Efthymios Papatzikis; Kyriakos Dimitropoulos; Kassandra Tataropoulou; Maria Kyrtsoudi; Elena Pasoudi; John M. O’Toole; Angeliki Nika (PLoS ONE, 2025)
This article reports the protocol of a single-arm exploratory study investigating the impact of singing on the brain activity of premature infants in the Neonatal Intensive Care Unit (NICU). The study focuses on how the differentiation of voices, as defined by the fundamental frequency (F0) shaped by biological sex and kinship, influences neurophysiological responses when measured by electroencephalography (EEG). Premature infants, who are highly sensitive to auditory stimuli, may benefit from music-based interventions; however, there is limited understanding of how voice variations between male and female caregivers, and whether they are biologically related, affect brain activity. Our protocol outlines a structured intervention where infants are exposed to singing by four facilitators – a male and a female music therapist, the mother, and the father – and includes two singing stages: a sustained note and a lullaby, both interspersed with silent periods to allow for baseline measurements. EEG recordings track brain activity throughout these sessions, followed by quantitative EEG (qEEG) analysis and thorough statistical computations (e.g., mixed-effects models, spectral power analysis, and post-hoc tests) to explore how these auditory stimuli influence brain function. Preliminary data from five infants show that maternal singing elicits the highest delta spectral power in all measured conditions except during the ‘lullaby song’, where paternal singing elicits the highest effects followed by the male music therapist and then the mother. These early findings highlight the potential influence of parental voices, particularly the fathers’ voice, on neonatal brain development, while the detailed study protocol ensures rigor and replicability, providing a robust framework for future research. (clinicaltrials.gov unique identifier: NCT06398912).